LONG-LIVED STRUCTURAL ENSEMBLES OF THE EAST EUROPEAN PLATFORM. Article 2. THE STRUCTURE OF THE TOP OF THE BASEMENT - S. Y. Kolodyazhny (Известия высших учебных заведений: Геология и разведка, 2018)
The basement’s top tectonics of the East European platform (EEP) has been considered on the basis of the modern mapping data. The importance of the long-lived tectonic zones that form the vortex megastructure has been justified.Their Riphean — early Vendian evolution was associated with activation of the Paleoproterozoic tectonic zones, which were transformed into paleorifts (aulacogens). The systems of the EEP aulacogens show the features of nonlinear structure and development: their evolution proceeded in the mode of transtension inside asymmetrically organized space between the active and passive paleocontinental margins; most of the paleorifts display wedge-shaped morphology, signs of asymmetric rifting and blocks rotation, a complex combination of elements of shear zones and gentle detachment zones tectonics, the vortex megastructure of the entire rifts system. Using an «iris diaphragm» model and the reconstructions with reversing plate rotation makes possible to explain the main patterns of the long-lived vortex structure of the EEP.